Um traço sobre o Atlântico : o Brasil na obra caricatural de Rafael Bordalo Pinheiro (1870-1905) - Brito, Romulo de Jesus Farias (2017)
In this thesis, an analysis of the caricature work of Rafael Bordalo Pinheiro (1846-1905) is made, in order to understand how this Portuguese intellectual showed several aspects related to Brazilian society in his satirical publications. Known as the greatest Portuguese caricaturist of the nineteenth century, Bordalo also worked professionally in Brazil between 1875 and 1879, but his compositions about the country precede this stay and extend for several years after his return to Portugal. Understanding how Brazil was presented throughout all these years, the elements that influenced the author's view of the country and the possible functions that such compositions have in their work are the main objectives of this work. The study is based on the hypothesis that Brazil constitutes a transnational axis of reflection in the work of the author, being used as an instrument to think the Portuguese society and, on the other hand, having its interpretation influenced by the conceptions of the caricaturist about Portugal, in a constant process of interlocution between the two shores of the Atlantic. In order to carry out such research, we will analyze compositions produced before, during and after the stay, present in the periodicals and albums of caricatures produced by Bordalo in both Portugal and Brazil.